(untitled) (Western European Journal of Historical Events and Social Science, 2026)
This article scientifically analyzes the formation, historical development of the family institution in Uzbekistan and its place in the system of national values. The family traditions, customs and social relations of the Uzbek people, which have been formed over the centuries, are covered on the basis of historical sources. Also, the strength of the family institution is considered as an important factor in the stability and spiritual development of society. The article analyzes the importance of the family in social, cultural and spiritual life from ancient times to the present day.